Trajectories of cognitive function development and predictive factors in disabled middle-aged and older adults - Jiaxue Pang; Yang Xu; Qiankun Liu; Juju Huang; Pengyao Li; Li Ma; Chunlu Zeng; Xiaoqing Ma; Hui Xie (Frontiers Media S.A., 2024)
ObjectiveTo explore the trajectories of cognitive function development and predictive factors in disabled middle-aged and older adults.MethodsUtilizing data from 983 disabled middle-aged and older adults in the China Health and Retirement Longitudinal Study (CHARLS) from 2013 to 2020, latent growth mixture models were constructed to analyze the categories of cognitive function development trajectories and their predictive factors.ResultsThe cognitive function trajectories of the disabled middle-aged and older adults were classified into three categories: rapid decline (32.6%), Slow decline (36.1%), and Stable (31.2%). Multinomial logistic regression analysis identified age, gender, residence, education, marital status, household income, sleep duration, depression, hearing ability, and social participation as predictors of these trajectories.ConclusionThere is heterogeneity in the cognitive function development trajectories among disabled middle-aged and older adults. Healthcare professionals can implement targeted health management based on the characteristics of different groups to prevent the deterioration of cognitive function in this population.